The Dialectics of Sudanese Arabic Literature Development: A Historical and Sociological Perspective - Rusdi, Mohammad (Kitabina: Jurnal Bahasa dan Sastra Arab, 2025)
Abstract: This research examines the development of Arabic literature in Sudan from historical and thematic perspectives. Through library research with a descriptive qualitative approach, this study traces the evolution of Sudanese literature from pre-colonial times to the contemporary era. The results show that Sudanese literature is rooted in a rich oral tradition, with poetry as the dominant form of expression. The development of the press in the early 20th century became a catalyst for the growth of modern Sudanese literature. Genres such as short stories and novels developed rapidly, addressing themes of national identity, social criticism, and resistance to authoritarian regimes. Prominent writers such as Tayeb Salih, Ibrahim Ishaq, and Rania Mamoun have made significant contributions in shaping Sudan's literary landscape. This research also reveals that Sudanese literature reflects the country's hybrid identity, combining Arab and African influences. In conclusion, Sudanese Arabic literature has undergone significant transformation, becoming an important medium in expressing socio-political realities and the complex search for national identity